Islamic Education Teacher Learning Strategy At Smk Karsa Mulya Palangka Raya During The Pandemic Through E-Learning Model - Surawan Surawan; Muhammad Redha Anshari; Linda Wirda Sari (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
The Covid 19 pandemic has a considerable impact not only on the economic decline of the Covid 19 pandemic community but also on learning in schools. Knowing that is initially face-to-face is transferred to an online learning model called E-Learning. This research aims to determine how PAI teachers' learning strategies in E-learning learning during pandemics like today. This research is descriptive qualitative research. The source of the data obtained by the researchers was an interview with Islamic religious education teacher SMK Karsa Mulya Palangkaraya. The result of this study is that learning through the E-learning model in SMK karsa mulya palangkaraya has its constraints for students, from the lack of activeness and discipline of students in using existing learning media.